Immunohistochemical Detection of p75 Neurotrophin Receptor (p75-NTR) in Follicular and Plexiform Ameloblastoma - YOITHAPPRABHUNATH THUKANAYAKANPALAYAM RAGUNATHAN (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Ameloblastoma holds a unique position among benign tumours by its locally destructive and invasive nature. Recently improvised molecular techniques helped researchers to unravel the myth behind such biologic behaviour. Though interesting findings have been delivered, the rhythmic correlation regarding the exact mechanism still remains lacking. Neurotrophins and their receptor mediated pathways play a crucial role in survival, death and differentiation of many neuroectoderm derived cells. With this background, the study has been aimed to investigate the expression of p75-NTR (Neurotrophin Receptor) in follicular and plexiform ameloblastoma. Aim: To analyze the immunohistochemical expression pattern of p75-NTR in ameloblastoma and to compare the immunohistochemical expression pattern of p75-NTR among the histological types of ameloblastoma, follicular and plexiform patterns. Materials and Methods: Total 22 ameloblastomas (12 follicular, 10 plexiform) were immuno-stained with anti-human p75-NTR mouse IgG monoclonal antibody and the pattern of staining is statistically analyzed. Results: Only 11 (10 follicular, 1 plexiform) out of 22 ameloblastomas showed immuno-reactivity to p75-NTR. In ameloblastoma, only the peripheral pre-ameloblast like tall columnar cells showed reactivity whereas the stellate reticulumlike cells were immuno-negative. The staining pattern was membranous in the immuno-reactive cells. The results were studied with the downstream pathways from the literature and a possible mechanism has been proposed. Conclusion: The expression pattern of p75-NTR was found to be more in follicular ameloblastoma than plexiform.